Special Issue from the 1st Greek Student Conference on Research and Science - Giannakopoulou, Aliki (Open Schools Journal for Open Science, 2019)
The first issue of the Open Schools Journal for Open Science created an interest in the education community in Greece and other European countries. The organisers of the 1st Student Conference on Research and Science that took place in Greece in March 2017 contacted the Journal editorial committee expressing their interest to present the conference findings to the wider journal community. This issue presents 44 articles written by students from across Greece in collaboration with their teachers/mentors. Below you will find a welcome note from the programme committee of the conference. All articles in this special issue are written in Greek.